EPCO-14. MULTIFACETED TRANSCRIPTOMIC AND PROTEOMIC ANALYSES IDENTIFIED PUTATIVE ALTERNATIVE SPLICING-DERIVED CELL SURFACE ANTIGENS IN GLIOMA. (12th November 2021) - Nejo, Takahide; Kwok, Darwin; Leung, Kevin; Wang, Lin; Wang, Albert; Watchmaker, Payal; Diebold, David; Driks, Hannah; Wells, Jim; Diaz, Aaron; Costello, Joseph; Okada, Hideho
Abstract: BACKGROUND: To develop effective immunotherapy for gliomas, it is crucial to expand the repertoire of targetable antigens. Recent studies have suggested that alternative splicing (AS), or its deriving tumor-specific junctions ("neojunctions"), could generate cryptic amino acid sequences that can be a source of neoantigens. In this study, we investigated neojunctions based on multifaceted transcriptomic and proteomic analyses, seeking the potential cell surface antigens that may be targeted by CAR. METHODS: For screening, we analyzed bulk RNA-sequencing data of TCGA-GBM/LGG with high tumor purity (n = 429) and GTEx normal tissues (n = 9, 166). Cohorts of spatially mapped intratumoral samples and longitudinally collected tumors were used to determine clonality and stability of the candidate neojunctions. Nanopore long-read amplicon sequencing was deployed to confirm the full-length transcript sequence. Their protein-level expression was explored by analyzing the Clinical Proteomic Tumor Analysis Consortium (CPTAC)-GBM proteomics dataset. RESULTS: In the screening analysis comparing TCGA and GTEx datasets, we identified 218 neojunctions with adequate expression, prevalence, and tumor-specificity. Of these, 12 were predicted to be cell-surface antigens. Eight of the 12, such as BCAN, DLL3, and PTPRZ1, were also observed in multiple cases of another validation dataset. In the analysis of tumors with spatially mapped intratumoral samples, 7 of the 12 were recurrently detected in no less than 50% of the samples in multiple cases. In addition, 5 of the 12 were found to be conserved in primary and recurrent pairs of tumors in multiple cases. Full-length transcript sequencing corroborated our predictions based on short reads, and also demonstrated more complex AS patterns. Finally, CPTAC-GBM proteomics analysis identified one cryptic peptide that substantiated the corresponding transcriptome-based prediction. CONCLUSION: We identified neojunctions with the potential to generate cell-surface antigens. These multifaceted transcriptomic and proteomic analyses provide the rationale to pursue the development of immunotherapy targeting neojunction-derived antigens.